Determination of γ‐hydroxybutyric acid in saliva by capillary electrophoresis coupled with contactless conductivity and indirect UV absorbance detectors. Issue 24 (20th October 2015) - Mazina, Jekaterina; Saar‐Reismaa, Piret; Kulp, Maria; Kaljurand, Mihkel; Vaher, Merike
Abstract : The aim of the current study was to optimise and validate the methodology for determination of γ‐hydroxybutyric acid (GHB) in saliva by CE combined with a contactless conductivity detector (C 4 D) and indirect UV absorbance detection (λABS = 210 nm). The optimized BGE, consisting of 8.5 mM maleic acid, 17 mM arginine, 255 μM cetyltrimethylammonium bromide (CTAB), and 15% acetonitrile, was evaluated for the separation of GHB in saliva within 6 min. The performance characteristics of the CE‐C 4 D‐indirect UV methodology was validated. The instrument detection and quantification limits were 0.49 and 1.6 mg/L for C 4 D, and 5.1 mg/L and 17.0 mg/L for indirect UV, respectively. The linearity was obtained over the range from 2.5 to 400 mg/L for C 4 D and from 12.5 to 400 mg/L for indirect UV. The interday precisions were within 2.3–5.7% and intraday precisions were within 1.6–9.0% for C 4 D as well as 2.1–9.3%, 5.6–10.1% for indirect UV in spiked saliva, respectively. The recoveries were within 87.2–104.4%. The matrix effects were +53.2% for small concentrations up to 25 mg/L for C 4 D and +23.6% for concentrations up to 75 for mg/L for indirect UV detection. No matrix effects were observed for higher concentration levels. In conclusion, CE‐C4D‐indirect UV can offer a rapid, accurate, sensitive, and definitive method for the determination of GHB abuse in saliva samples as a forensic screening tool.